“Vida dupla”? : A poética musical de Miklós Rózsa e sua aplicação nas músicas de filmes e de concertos - Freitas, Hugo Leonardo Morais de (2016)
Miklós Rózsa claimed to keep a "double life": composer of concert music versus composer of films soundtrack. In this paper, we sought to answer questions such as: would have the composer really a "double life" articulated this way? His work would have a consistent poetic of music, common to both genres to which the composer had dedicated himself? It is known that Rózsa had the Hungarian folk music as basis for his music. To better understand them was made a profound bibliographic research on the subject, in which several articles of Hungarian musicologists were used in order to give more consistency to it. With the aim of to see if Rózsa maintained the same musical poetic in both genres, were realized several comparative analyzes of the composer's works, both in his movies soundtracks as in his concert music, to cover all productive periods of the composer (opus 1-1927 to opus 451989), period which he also worked in several companies and composed for various filmic genres (drama, fantasy, comedy, noir, thriller, epic, among others). Prior to the preparation of this work, there was the assumption that the composer would have a consistent musical poetics in the two musical genres to which he was dedicated. Thus, another question would arise: Did Rózsa innovate the Hollywood filmic music or did he adapt himself to it? To answer this question, it was necessary also to investigate the characteristics of the soundtracks of Hollywood movies before the arrival of the Hungarian composer to the Californian district.